Assessing the clinical outcomes of immunotherapy and docetaxel combinations in metastatic castration-resistant prostate cancer: a meta-analysis - Azka Syed; Hasan Raza; Hameer Khan Khaskheli; Izza Rafique; Sameen Shahid; Nimra Shahzadi; Abdelrahman Sayed Al Komi; Abdullah A. Assiri; Muhammad Abbas Khokhar; Najeeb Ullah Khan (BMC Cancer)
Abstract Background Despite breakthroughs in treatment, metastatic castration-resistant prostate cancer (mCRPC) continues to pose a substantial problem. This meta-analysis sought to assess the efficacy and safety of immunotherapy-chemotherapy combinations in mCRPC. Methods A thorough search of ClinicalTrials.gov, Embase, PubMed, SCOPUS, and Web of Science was performed to retrieve randomised controlled trials (RCTs) published between January 2000 and July 2024. The primary outcomes included overall survival (OS), progression-free survival (PFS), PSA response rate, time to PSA progression, and severe adverse events (SAEs). Data were aggregated using fixed-effect or random-effects models dependent on heterogeneity. Results Four RCTs involving 2,289 participants were included. The pooled results showed no statistically significant advantage of immunotherapy-chemotherapy combinations over placebo or docetaxel alone for OS (HR = 0.95; 95%CI: 0.79–1.14; P = 0.56), PFS (HR = 0.93; 95%CI: 0.80–1.07; P = 0.32), PSA response rate (RR = 0.99; 95%CI: 0.66–1.49; P = 0.96), time to PSA progression (HR = 1.01; 95%CI: 0.90–1.14; P = 0.85). The risk of SAEs was also not significantly different between the intervention and control groups (RR = 0.95; 95%CI: 0.71–1.29; P = 0.76). Conclusion Existing findings do not suggest a significant advantage of immunotherapy-chemotherapy combos over chemotherapy alone in mCRPC. However, the small number of trials and study heterogeneity call for caution in interpretation. Further high-quality RCTs are required to determine the role of these combinations in mCRPC treatment.